Law of humanity project : a story of international law reform and state-making - Soirila, ukri (London [England] : HART PUBLISHING, 2021)
"This book provides the first comprehensive introduction to the role of humanity in international law, offering a fresh perspective to a discussions with global implications. The 1990s and the first decade of the twenty-first century witnessed the sporadic emergence of a new vision of global law. Although the vision has taken many different forms, all instances of it have been uniform in the attempt of radically altering how we understand international law by seeking to posit the human as the primary subject of the international legal order and humanity as its main source of legitimacy. Together, this book calls these instances "the law of humanity project". In so doing, it also paints a picture of and critically assesses a particular moment in the history of international law - a moment which may have already come to a sudden end as a consequence of the current populist backlash in world politics, but during which it seemed inevitable that the law of humanity vision would come to play an increasingly important role in world affairs."--
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Keywords: Public international law; Electronic books